MODEL PENGEMBANGAN KUALITAS PRODUK DALAM RANGKA MERAIH KEPERCAYAAN DAN LOYALITAS KONSUMEN - Agus Budi Purwanto (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2014)
The background of this research is the declining quality of UKM products . This indicates that UKM can not win the trust and loyalty of consumers . In general, this study aimed to determine the effect of the Product Quality to Consumer Loyalty in which the Trust as an intervening variable. Specifically , this research aims to improve the competitiveness of UKM . Research data collection techniques by means of spreading consumer questionnaire systematically arranged with several possible answers were easy to understand . Distribution of the questionnaire by means of a direct encounter conducted in the period February to March 2014 with a sample of some 82 people. Then the data were collected through a questionnaire to test the data analyst; validity and reliability, followed by a simple regression analysis and multiple regression analysis. The results of the study demonstrate that 1 ) There is a positive and significant effect between the product quality to consumer trust. 2 ) Trust positive and significant impact on consumer loyalty . 3 ) The results also prove that the product quality indirect effect on loyalty to the trust as intervening.